A Footnote to Sport History: Twenty Years of Cricket, Conflict and Contestation in Samoa, 1880–1900. Issue 14 (22nd September 2017) - Sacks, Benjamin
Abstract: During the late-nineteenth century, imperial expansion increasingly produced what Louise Pratt terms 'contact zones' – 'social spaces where cultures meet, clash and grapple with each other, often in contexts of highly asymmetrical relations of power'. Sport was one of the most visible spaces where this process took place. This paper uses the example of cricket in Samoa to demonstrate how different groups sought to control sport's meaning amidst great uncertainty. Almost as soon as they began playing cricket, Samoans radically altered its method and meaning to create the distinctively Samoan game of kirikiti . This act established the cricket pitch as a 'contested space' between Samoans and foreigners, who were wary of kirikiti's association with Samoan politics and customary exchange. As was the case in Samoa more generally, however, this struggle was not neatly divided between Samoans and foreigners. While missionaries and settlers portrayed the game as a threat, others – notably sailors and proponents of British influence – greeted it with relative enthusiasm. For their part, Samoans used the game to signal alignment with or against one or another Western power. Finally, Samoa's growing 'mixed-race' community saw the game as a means of confirming their place in both the Samoan and European 'worlds'.